2006
DOI: 10.1021/jf061340s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proteins in Oil-in-Water Emulsions on the Stability of Lipid Hydroperoxides

Abstract: The purpose of this research was to better understand the mechanisms by which proteins affect the rates of lipid oxidation in order to develop protein-stabilized emulsion delivery systems with maximal oxidative stability. This study evaluated the affect of pH and emulsifier concentration on the stability of cumene hydroperoxide in hexadecane-in-water emulsions stabilized by beta-lactoglobulin (beta-Lg). Emulsions prepared with 0.2 wt % beta-Lg (at pH 7.0) showed a 26.9% decrease in hydroperoxide concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…The obtained results correspond very well with previously mentioned publications by many authors about the inhibition by water the hydrocarbons oxidation reactions [31][32][33][34][35][36][37][38][39]. It is known that in keeping with the theory of liquid-phase oxidation the oxidation of hydrocarbons with molecular oxygen occurs by the chain free-radical mechanism and proceeds via a stage of hydroperoxides or peroxides formation, which should participate in a chain branching processes [31][32][33][34].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The obtained results correspond very well with previously mentioned publications by many authors about the inhibition by water the hydrocarbons oxidation reactions [31][32][33][34][35][36][37][38][39]. It is known that in keeping with the theory of liquid-phase oxidation the oxidation of hydrocarbons with molecular oxygen occurs by the chain free-radical mechanism and proceeds via a stage of hydroperoxides or peroxides formation, which should participate in a chain branching processes [31][32][33][34].…”
Section: Resultssupporting
confidence: 89%
“…A number of authors showed that, in the presence of natural surfactants (sulphur, oxygen and nitrogen compounds) in the hydrocarbons medium, hydroperoxides, as amphiphilic compounds possessing surface activity, create H-bonds with the water and, as result of that, absorb on the hydrocarbons/water emulsion boundary with the formation of reverse micelles. Peroxides involved into micelles become more stable and the rate of their decomposition with free radicals formation decreases and as result of that the total reaction rate decreases as well [36][37][38][39]. Csanyi et al reported that in the presence of high water concentrations an overall rate of oxidation decreases, because of the competing formation of the cyclic hydro-peroxide dimers which are kinetically less active [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower formation of primary oxidation products can be attributed to the presence of whey proteins which, in emulsions, are reported to possess antiradical activity and also to play a synergistic effect with phenolic antioxidant compounds. 34,35 It must also take into consideration that protein-stabilized interfaces are usually characterized by higher elasticity modulus and surface viscosity 36 and it is thus likely that a more rigid membrane could have hindered the hydroperoxides migration from the interior of the lipid droplet to the aqueous phase. Such a result is in agreement with what was previously reported by other authors 35 even though controversial results are also reported.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…12 Since food proteins have been shown to have good antioxidant properties, 13,14 incorporating emulsified oil into the dispersed protein-rich phase should help protect against lipid oxidation.…”
Section: Introductionmentioning
confidence: 99%